Pendidikan pelbagai budaya untuk merealisasikan negara bangsa '1 Malaysia': Perspektif Islam dan Barat / Zulkifli Dahalan and Hazri Jamil - Dahalan, Zulkifli; Jamil, Hazri (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2011)
This paper aims at elucidating a discussion about the importance of multi-cultural education in the context of a Malaysian pluralistic society. Besides, the sights of Islam and the West towards the concept of cultural diversity are elaborated in addition to the role of education in fostering understanding and acceptance of cultural diversity that exists within a pluralistic society in Malaysia. In fact, the discussion represents a discourse of ideas to raise the awareness of understanding and accepting the diversity and differences in beliefs, religion, norms and cultural values in the Malaysian modern society. Accordingly, several approaches, to implement the elements of multicultural education in the existing educational system, are suggested to increase the awareness and understanding among young people of cultural diversity of this country.